1993
DOI: 10.1111/j.1432-1033.1993.tb18207.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of two related genes encoding the 56‐kDa and 123‐kDa subunits of trehalose synthase from the yeast Saccharomyces cerevisiae

Abstract: Preparations of intact trehalose synthase contain three polypeptides with molecular masses of 56, 102 and 123 kDa. We have cloned the genes TSSl and TSLl coding for the 56-and 123-kDa subunits, respectively. These genes are located on chromosomes I1 (TSSI) and XI11 (TSLI). The TSSl gene was found to be identical with ClFl, a gene required for normal growth on glucose. The product of the entire TSSl gene exibits 37% identity with a 502-amino-acid stretch from the middle of the TSLl product. Disruption of the TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
127
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(130 citation statements)
references
References 45 publications
(45 reference statements)
3
127
0
Order By: Relevance
“…A variety of biochemical data suggest that Tps1, Tps2, and Tsl1 interact intimately with each other to form the Tre6P synthase/phosphatase complex (Bell et al, 1992;De Virgilio et al, 1993;Vuorio et al, 1993;Londesborough and Vuorio, 1993). Based on its homology to Tsl1, a fourth protein, Tps3, may also be part of this complex (De Virgilio et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of biochemical data suggest that Tps1, Tps2, and Tsl1 interact intimately with each other to form the Tre6P synthase/phosphatase complex (Bell et al, 1992;De Virgilio et al, 1993;Vuorio et al, 1993;Londesborough and Vuorio, 1993). Based on its homology to Tsl1, a fourth protein, Tps3, may also be part of this complex (De Virgilio et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…The biochemical and genetic data available suggest that the three proteins Tps1, Tps2, and Tsl1 form a multimeric protein complex (Bell et al, 1992;De Virgilio et al, 1993;Vuorio et al, 1993;Londesborough and Vuorio, 1993). In the present study we have performed a series of experiments to further elucidate the structural composition of the Tre6P synthase complex as well as the specific role of its potential subunits.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Genes encoding the first of these enzymes (tps) have been identified in a wide range of organisms, including plants (e.g., Selaginella lepidophylla [8]), invertebrates (e.g., Caenorhabditis elegans [9]), yeast (e.g., Saccharomyces cerevisiae [10,11]) and bacteria (e.g., Escherichia coli [12]); trehalose-6-phosphate phosphatase genes have also been characterised for many micro-organisms. Although some of these organisms are anhydrobiotic (e.g., Se.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of trehalose is mediated by the trehalose-6-phosphate (Tre6P) synthase-phosphatase complex, which, in S. cerevisiae, consists of at least four subunits carrying either Tre6P synthase (Tps1), Tre6P phosphatase (Tps2) or regulatory activities (Tps3 and Tsl1; Bell et al, 1992;De Virgilio et al, 1993;Vuorio et al, 1993;Reinders et al, 1997). In accordance with the observation that heat-induced accumulation of trehalose is partially dependent on protein synthesis in S. cerevisiae (De Virgilio et al, 1991), both catalytic subunits (Tps1 and Tps2) have been shown to be hsps, and expression of all four genes encoding the subunits of the Tre6P synthase complex (TPS1, TPS2, TPS3 and TSL1 ) has been found to be dramatically enhanced under heat-shock conditions (De Virgilio et al, 1993;Winderickx et al, 1996).…”
Section: Introductionmentioning
confidence: 99%